POTENTIAL ANALYSIS OF THE BIOLARVACIDAL PLANT ON Aedes aegypti FROM THE COMMUNITY YARD OF GUNUNGPUYUH SUB-DISTRICT, SUKABUMI CITY - Hilda Munadiah; Muhammad Nur Azzura Saraesa; Jujun Ratnasari (JBIO: jurnal biosains (the journal of biosciences), 2024)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes sp. mosquito. This disease is one of the main problems in Indonesia. Sukabumi is one of the cities in West Java that has the highest case di DHF. Chemical larvicides were used to control the Aedes aegypti mosquito. But its cause resistance in mosquito larva, so the seek for alternatives larvicides from natural and environmentally friendly are sought. Many studies had carried out on alternatives larvicides derived from natural product (biolarvicides). Natural larvicides have one advantage, that they do not cause resistance in mosquitoes. Several studies on biolarvicides are summarized to obtain information on several plants planted by the community in Gunungpuyuh District, Sukabumi City, which have the potential as biolarvicides. Of the 343 species of plants planted by the community, seven species of plants have high effectiveness with an LC (Median Lethal Concentration) LC50 value of <750 ppm. Lemongrass, cucumber, soursop, and kaffir lime were plants that potencial as biolarvicides compared to the others with LC50 values of 1.553 ppm, 189.261 ppm, 279.882 ppm, and 603 ppm. This plant is easy to cultivate and can be used as a biolarvicides by the community.